The Sharpen Role of Community Health Center and Clinic Accreditation Surveyors (Literature Review) - Ahyar Wahyudi; Friedrich Max Rumintjap; Siswanto Pabidang (Formosa Journal of Science and Technology, 2023)
The quality of health services has long been a central topic in discussions regarding health system optimization. As a basis, Hippocrates, known as the "Father of Medicine", provided a fundamental principle: "Primum non nocere" or "first of all, do no harm" (Hippocrates, n.d.). This principle not only reminds medical personnel to heal, but more than that, prioritizes the safety and welfare of patients. Making connections with philosophical thought, Immanuel Kant, one of the leading philosophers, emphasized the importance of treating humans as ends, not as means (Kant, 1785).